Pengaruh Kreativitas Iklan Dan Celebrity Endorser Terhadap Efektifitas Iklan Aplikasi Shopee - Dinda Charomatul Hidayah (Communicology: Jurnal Ilmu Komunikasi, 2021)
ABSTRACT One of the e-commerce that currently exists is constantly thinking about how to make effective advertisements, by making creative advertisements and using good celebrity endorsements. The purpose of this study is to prove whether advertising creativity and celebrity endorser together (simultaneously) have a significant effect on the effectiveness of Shopee application advertising (Case Study on Communication Studies students, University of 17 August Surabaya). The population in this study were all students of Communication Studies at 17 August Surabaya, class of 2016-2019, totaling 1,230 students and using a sample of 93 students. The method used is multiple linear regression analysis. Based on the results of multiple linear regression analysis, it is found that the advertising creativity variable (X1) and celebrity endorser (X2) either partially or simultaneously has a significant effect on advertising effectiveness, it is indicated by a significance value of 0.000 below 0.0. Based on partial analysis, it turns out that the results of this study indicate that the tcount value of 7387 is greater than ttable of 1.98667 and the significance value of 0.000 is smaller than 0.05, it means that advertising creativity (X1) has an effect on the effectiveness of advertising (Y). This means that the presence of advertising creativity makes the audience pay attention to the advertisement in detail and detail so that confidence arises in the audience to make transactions using the goods/services, thereby showing that advertising creativity (X1) affects the effectiveness of advertisements (Y). Keywords: Advertising Creativity; Advertising Effectiveness; Celebrity Endorser